2010
DOI: 10.1007/s00253-010-2763-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversities on unaged and aging flue-cured tobacco leaves estimated by 16S rRNA sequence analysis

Abstract: Flue-cured tobacco leaves (FCTL) contain abundant bacteria, and these bacteria play very important roles in the tobacco aging process. However, bacterial communities on aging FCTL are not fully understood. In this study, the total microbial genome DNA of unaged and aging flue-cured tobacco K326 were isolated using a culture-independent method, and the bacterial communities were investigated by restriction fragment length polymorphism analysis. Comparison of the number of operational taxonomic units (OTUs) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 22 publications
4
74
0
Order By: Relevance
“…The bacteria were Corynebacterium bovis, Micrococcus luteus, Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis and Pseudomonas aeruginosa while the fungi were Aspergillus niger, Rhizopus stolonifer, Alternaria alternata, Geotrichum candidum, Aspergillus flavus and Penicillium italicum ( Table 2). Rubinstein and Pederson [15] and Yang et al [16] isolated bacteria, yeasts and molds in their different types of snuff. Pseudomonas aeruginosa and Staphylococcus aureus were also identified in bacteriological examinations of the sputum samples of a patient with chronic bronchitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacteria were Corynebacterium bovis, Micrococcus luteus, Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis and Pseudomonas aeruginosa while the fungi were Aspergillus niger, Rhizopus stolonifer, Alternaria alternata, Geotrichum candidum, Aspergillus flavus and Penicillium italicum ( Table 2). Rubinstein and Pederson [15] and Yang et al [16] isolated bacteria, yeasts and molds in their different types of snuff. Pseudomonas aeruginosa and Staphylococcus aureus were also identified in bacteriological examinations of the sputum samples of a patient with chronic bronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…The patient used snuff and it was theorized that the snuff might have been the source of the pathogens. A study was undertaken on twenty one samples of previously unopened packs of snuff [16]. They isolated Bacillus subtilis, Staphylococcus aureus, Staphylococcus albus and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the residues detected in soil reached below 0.045 mg/kg 21 days after the last treatment. As the cured tobacco leaves are not suitable for cigarette products because of its disagreeable odor and undesirable aroma, the aging process of tobacco is necessary after flue-curing, which is a key step to improve tobacco aroma quality and to increase its usability (Huang et al 2010). Normally, the cured tobacco leaves need to be aged for 2-3 years before they are manipulated again.…”
Section: Resultsmentioning
confidence: 99%
“…Early reports, mostly by investigators of the tobacco industry, performed identification and quantification of bacteria and fungi in fresh and processed tobacco, using cultivationbased methods [15]. Recently, 16S rRNA-based techniques including random fragment length polymorphism (RFLP), denaturing gradient gel electrophoresis (DGGE), single strand conformation polymorphism (SSCP) and sequencing have been used to characterize bacterial communities in fresh and cured tobacco leaves as well as those associated with tobacco fermentation process [16][17][18][19][20]. These studies revealed great deal of diversity and differences in the composition of microbiota associated with the different forms of tobacco.…”
Section: Introductionmentioning
confidence: 99%